Cell Cycle Regulation Meets Tumor Immunosuppression. Issue 10 (October 2020) - Li, Jinyang; Stanger, Ben Z.
Abstract : Reciprocal interactions between tumor cells and immune cells shape the tumor microenvironment. Recent studies indicate that enhanced cell cycle activity in cancer cells suppresses antitumor immunity. Herein we discuss potential mechanisms by which cell cycle programs intrinsic to tumor cells are coupled to immune behavior, with consequences for immunotherapy.